THE UTILIZATION OF REPETITION DRILL OF AUDIO-LINGUAL METHOD FOR TEACHING PRONUNCIATION OF ENGLISH VOWELS - Muhyiddin Aziz; Alief Sutantohadi; Eda Maaliah (Universitas Katolik Widya Mandala Surabaya, 2020)
Pronunciation is one of the most important indicators of speaking and listening skill. It canchange the meaning of words and sentences when they are mispronounced. The features ofpronounciation can be devided into two such as segmental and supra segmental features.Segmental features consist of vowels and consonant while supra segmental features consist ofstress, intonation, and connected speech. The research was conducted at Madiun StatePolytechnic. The participants are the students of englis study program B class consisting of27 students in the academic year of 2018/2019. The Method of this research was RepetitionDrill of Audio-lingual Method. The aims of this research are; 1)to know that Repetition Drillof Audio-lingual Method can improve the students’ pronunciation of English vowels and 2) todescibe the process of teaching and learning activities of english pronunciation throughRepetition Drill of Audio-lingual Method. The qualitative and quantitative data were used inthis research. Qualitative data were taken from the scores of the pre-test of 27 students fromB class and all cycles of the research. The qauntitative data were taken through theobservation, interview, and questionnaire. Based on findings, discussions, and conclusions,The Repetition Drill of Audio-lingual Method is recomended to improve the english vowelspronunciation of the Second Semester of English Study Program of Madiun State Polytechnicin the Academic Year of 2018/2019.Keywords: Repetition Drill, Audio-lingual Method, Pronunciation, Vowels.